Quantitative assessment of the degradation of aggregated TDP‐43 mediated by the ubiquitin proteasome system and macroautophagy. Issue 12 (25th August 2017) - Cascella, Roberta; Fani, Giulia; Capitini, Claudia; Rusmini, Paola; Poletti, Angelo; Cecchi, Cristina; Chiti, Fabrizio
ABSTRACT: Amyotrophic lateral sclerosis and frontotemporal lobar degeneration with ubiquitin‐positive inclusions are neurodegenerative disorders that share the cytosolic deposition of TDP‐43 (TAR DNA‐binding protein 43) in the CNS. TDP‐43 is well known as being actively degraded by both the proteasome and macroautophagy. The well‐documented decrease in the efficiency of these clearance systems in aging and neurodegeneration, as well as the genetic evidence that many of the familial forms of TDP‐43 proteinopathies involve genes that are associated with them, suggest that a failure of these protein degradation systems is a major factor that contributes to the onset of TDP‐43–associated disorders. Here, we inserted preformed human TDP‐43 aggregates in the cytosol of murine NSC34 and N2a cells in diffuse form and observed their degradation under conditions in which exogenous TDP‐43 is not expressed and endogenous nuclear TDP‐43 is not recruited, thereby allowing a time zero to be established in TDP‐43 degradation and to observe its disposal kinetically and analytically. TDP‐43 degradation was observed in the absence and presence of selective inhibitors and small interfering RNAs against the proteasome and autophagy. We found that cytosolic diffuse aggregates of TDP‐43 can be distinguished in 3 different classes on the basis of their vulnerability to degradation, which contributed to the definition—with previous reports—of a total of 6 distinct classes of misfolded TDP‐43 species that range from soluble monomer to undegradable macroaggregates. We also found that the proteasome and macroautophagy‐degradable pools of TDP‐43 are fully distinguishable, rather than in equilibrium between them on the time scale required for degradation, and that a significant crosstalk exists between the 2 degradation processes.—Cascella, R., Fani, G., Capitini, C., Rusmini, P., Poletti, A., Cecchi, C., Chiti, F. Quantitative assessment of the degradation of aggregated TDP‐43 mediated by the ubiquitin proteasome system and macroautophagy. FASEB J. 31, 5609–5624 (2017). www.fasebj.org